Legal Construction of Immaterial Compensation for Telecommunication Service Users Due to Violations of Consumer Rights - Putri Handayani Nasution (Rechtsvinding, 2026)
The development of information and communication technology has made telecommunications services a vital necessity in people's lives. The high dependence on telecommunications services requires providers to ensure the availability of quality, safe, continuous services that comply with consumer rights. However, in practice, telecommunications service users still have the potential to experience losses due to service disruptions, system failures, misuse of personal data, information leaks, or disproportionate service terminations. These losses are not only material but can also include immaterial losses, such as discomfort, anxiety, loss of security, disruption of privacy, and psychological stress. This study aims to analyze the legal construction of providing compensation for immaterial losses to telecommunications service users due to violations of consumer rights. This study uses a normative juridical method with a statutory and conceptual approach. The results show that the legal liability of telecommunications service providers can be constructed through an integration of consumer protection law, civil law, telecommunications law, and personal data protection. However, there are no comprehensive parameters regarding the proof and assessment of immaterial losses. Therefore, it is necessary to strengthen the legal construction oriented towards the restoration of rights, legal certainty, and substantive justice for consumers